2003
DOI: 10.1093/sleep/26.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Position on Snoring in Apneic and Nonapneic Snorers

Abstract: This study demonstrated that the positional dependency is different between nonapneic snorers and OSA patients. Most of the nonapneic snorers snore less in the lateral position than in the supine position in contrast to OSA patients who often fail to decrease snoring even in the lateral position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 15 publications
6
48
4
2
Order By: Relevance
“…8,13,36,37,39 However, our findings ( Figure 5B) do not support earlier studies claiming that snoring intensity is higher in SWS. 36,39 In our subjects AHI ranged from 0.3 to 80 (events/h) and mean individual breathing intensity ranged from 20 to 65 (dB); however, no correlation was found between mean (or upper quarter or top 1%) breathing or snoring intensity and AHI. Our finding is in contrast to earlier reports that found that snoring intensity positively correlated with AHI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…8,13,36,37,39 However, our findings ( Figure 5B) do not support earlier studies claiming that snoring intensity is higher in SWS. 36,39 In our subjects AHI ranged from 0.3 to 80 (events/h) and mean individual breathing intensity ranged from 20 to 65 (dB); however, no correlation was found between mean (or upper quarter or top 1%) breathing or snoring intensity and AHI. Our finding is in contrast to earlier reports that found that snoring intensity positively correlated with AHI.…”
Section: Discussioncontrasting
confidence: 99%
“…It is generally accepted that snoring and AHI are very dependent on the body position. 39 Further studies are needed to explore the effect of body position on breathing and snoring sound characteristics. We used a noncontact microphone to record breathing and snoring sounds because this approach enables more natural sleep that is not affected by equipment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alarms were infrequent and of short duration during active treatment. Of particular note is that snoring frequency did not change with active treatment, a finding consistent with another report, 38 and difficult to reconcile on the basis of increased wake time. Finally, if AHI on active treatment exclusively represents nonsupine events without changes in wake time, the addition of 19% supine time (ST) to a non-supine AHI (AHI NS ) of ~14 events/h with a 5.3-fold higher supine versus non-supine AHI ratio (AHI Ratio ) would be expected to increase total AHI to ~25 events/h (Expected AHI Total = AHI NS × AHI Ratio × ST + AHI NS × (1-ST) = 14 × 5.3 × 0.19 + 14 × 0.81 = 25.4).…”
Section: Methodological Considerationssupporting
confidence: 77%
“…It was shown that the body position during sleep changes both duration and intensity of snoring sounds [27]. However, we did not find a consistent and significant relationship between the sleeping position and the change in the linearity of snoring sound generating process.…”
Section: Resultscontrasting
confidence: 90%
“…The LOOCV is a common technique when the number of observations (subjects in this case) is relatively small; it helps to prevent over-fitting. In the LOOCV, one observation is used as testing set and the rest [27] is used as training set. This procedure is repeated for all observations [28] and the average performance is measured.…”
Section: Classificationmentioning
confidence: 99%